Childhood Obesity Task Forces Established by State Legislatures, 2001-2010 - Ashleigh L. May, MS, PhD; Sonia A. Kim, PhD; Bettylou Sherry, RD, PhD; Heidi M. Blanck, MS, PhD (Centers for Disease Control and Prevention, 2013)
Introduction States and communities are considering policy and environmental strategies, including enacting legislation, to reduce and prevent childhood obesity. One legislative approach has been to create task forces to understand key issues and develop a course of action. The goal of this study was to describe state-level, childhood obesity task forces in the United States created by legislation from 2001 through 2010. Methods We used the Center for Disease Control and Prevention's Division of Nutrition, Physical Activity, and Obesity database to identify state-level childhood obesity task forces created through legislation from 2001 through 2010. Results We identified 21 states that had enacted legislation creating childhood obesity task forces of which 6 had created more than one task force. Most task forces were charged with both gathering and reviewing information and making recommendations for obesity-prevention actions in the state. Most legislation required that task forces include representation from the state legislature, state agencies, community organizations, and community members. Conclusion Evaluation of the effectiveness of obesity-prevention task forces and the primary components that contribute to their success may help to determine the advantages of the use of such strategies in obesity prevention.